1981
DOI: 10.1111/j.1365-2923.1981.tb02481.x
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of interneship training in Sri Lanka

Abstract: The internship period is a critical phase in the continuum of training provided to medical students. An analysis was made of the tasks the intern medical officers in Sri Lanka are engaged in during their period of training in different clinical disciplines. Data was collected by direct observations by trained observers for a continuous period of 10 days and self-reporting by the interns at the two teaching hospitals and four of the provincial hospitals where interns are posted. The reliability of the data was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The needs assessment confirms that internship for Sri Lankan doctors is a stressful undertaking for which they feel underprepared as is common with medical graduates around the world [28]. The lack of communication skills, identified in this study, is especially concerning since it has the potential to extend beyond the internship period affecting both doctorpatient contact and the personal lives of the participants.…”
Section: Discussionsupporting
confidence: 57%
“…The needs assessment confirms that internship for Sri Lankan doctors is a stressful undertaking for which they feel underprepared as is common with medical graduates around the world [28]. The lack of communication skills, identified in this study, is especially concerning since it has the potential to extend beyond the internship period affecting both doctorpatient contact and the personal lives of the participants.…”
Section: Discussionsupporting
confidence: 57%
“…However, it would have been interesting to determine the responses of the internes in the more outstation hospitals in Sri Lanka on this point. An earlier study of interneship revealed that the internes in such outstation hospitals were granted a much greater degree of responsibility for most tasks in comparison with the internes in the teaching hospitals and the larger provincial hospitals in the country (Abeykoon et al , 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Obstetrics and gynaecology and paediatrics are considered as surgery and medicine appointments respectively. An earlier study of the interneship has pinpointed the deficiencies in this scheme (Abeykoon et al , 1981) and since then they have been reinforced with respect to obstetrics and gynaecology (Rodrigo, 1981). The suggestion has been made by the latter as well as by the Faculties of Medicine at Peradeniya and Colombo that a restructuring of the interneship to include training in all four major clinical disciplines and, preferably, also in community medicine is appropriate for Sri Lanka's requirements of health care delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MEU Peradeniya conducted a research study on internship [8] and made recommendations for follow up. The internship is an important year for medical graduates to decide on their choice of future career in medicine.…”
Section: Post Graduate Training and Specializationmentioning
confidence: 99%